Numerical evaluation of material type on topology optimization of thin square plates - EVRAN, SAVAŞ (My University, 2024)
This numerical paperincluding topology optimization methoddeals with the investigationthe impactof the material type on final mass as topology density and the total deflection of thin square plates underclamped-freeboundary conditions. The clamped boundary condition was employed at the bottom edge of each plate, whereas the other edges were considered as free. Variouscompressive forcessuch as 5kN and 7 kN in numerical analyseswere applied to top edge of square plates. Numerical determinations were conducted by thestatic structure and topology optimization in ANSYS WORKBENCHcommercial software. The final massresultsforsquare plates in topology optimization werefoundin accordance withvon Mises stress datacalculated. The numerical resultsshow thatthe lowestfinal mass and highestdeflectiondataof thin square plates were foundin accordance withMagnesium Alloy, Aluminum Alloy, Copper Alloy, and Structural Steel, respectively.The highest and lowest mass reduction results in the topology optimization were obtained utilizing Magnesium Alloy and Structural Steel, respectively. Keywords:Deformation; Finite Element Method; Material; Stress; Topology optimization
Keywords: Makina Mühendisliği; Enerji; Makina Teorisi ve Dinamiği; Mekanik; Sonlu Elemanlar Yöntemi; Havacılık ve Uzay Mühendisliği; Uzay Mühendisliği; Görev; Matematiksel Modelleme teknikleri; Mühendislik ve Teknoloji; Mechanical Engineering; Energy; Machine Theory and Dynamics; Mechanical; Finite Element Methods; Aeronautical and Space Engineering; Space Engineering; Task; Mathematical Modeling Techniques; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; ASTRONOMİ VE ASTROFİZİK; MÜHENDİSLİK, HAVACILIK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ENGINEERING, MECHANICAL; ENERGY & FUELS; ASTRONOMY & ASTROPHYSICS; ENGINEERING, AEROSPACE; Astronomi ve Astrofizik; Fizik ve Astronomi (çeşitli); Genel Fizik ve Astronomi; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; Astronomy and Astrophysics; Physics and Astronomy (miscellaneous); General Physics and Astronomy; Computational Mechanics; Automotive Engineering; Aerospace Engineering; Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences; Deformation; Finite Element Method; Material; Stress; Topology optimization